1968
DOI: 10.1002/1097-0142(196807)22:1<151::aid-cncr2820220118>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic neuroectodermal tumor of infancy

Abstract: Two cases of melanotic neuroectodermal tumor (melanotic progonoma) of in fancy are presented. In one, the tumor involved the temporal bone, which, to our knowledge, has not been previously reported. The histochemical enzyme pattern of these tumors is compared with that of certain other tumors thought to be derived from cells of the neural crest. The authors' findings offer further support for neural crest origin of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Demonstration on an elevated urinary vanilmandelic acid level in a patient with the tumor by Borello & Gorlin (1966) is of particular importance, because such a finding has been reported only in tumors thought to be of neural crest origin. Koudstaal et al (1968) have offered further support for the neuroeetodermal theory by comparing the histochemieal enzyme pattern of this tumor with that of certain neural crest tumors. Although several investigators have demonstrated the presenee of nerve cells and neurofibrils in such tumors light microscopically (Martin & Foote 1951, MacDonald & White 1954, Nathanson & Tedeschi 1967), many others have failed to identify any tieural elements.…”
Section: Discussionmentioning
confidence: 92%
“…Demonstration on an elevated urinary vanilmandelic acid level in a patient with the tumor by Borello & Gorlin (1966) is of particular importance, because such a finding has been reported only in tumors thought to be of neural crest origin. Koudstaal et al (1968) have offered further support for the neuroeetodermal theory by comparing the histochemieal enzyme pattern of this tumor with that of certain neural crest tumors. Although several investigators have demonstrated the presenee of nerve cells and neurofibrils in such tumors light microscopically (Martin & Foote 1951, MacDonald & White 1954, Nathanson & Tedeschi 1967), many others have failed to identify any tieural elements.…”
Section: Discussionmentioning
confidence: 92%
“…Borello and Gorlin (1966), however, found in their case high urinary levels of vanilmandelic acid, a characteristic of various tumours derived from neural crest cells. Consequently they suggested that the tumour was of neural crest origin, a theory that Koudstaad et al (1968), with their comparative enzyme histochemical methods, confirmed, and which is now the most widely accepted.…”
Section: Commentmentioning
confidence: 98%